Image information measurement for video retrieval - Qing-sheng YUAN; Dong-ming ZHANG; Guo-qing JIN; Fei LIU; Xiu-guo BAO (Tongxin xuebao)
To meet the speed and performance requirements, Sub-region entropy based image information measurement (SEII)method was proposed, which integrates the salie region detection, region division and features fusion. And, performance evaluation method was designed and many experiments were carried out, proving SEII coordinates with human vision evaluation.Also,SEII is evaluated in a real video retrieval system,which shows increase about 4.4% of mAP with 1.5 times speedup.